Sustainable Agriculture and Food Security Aspects of Euro-Mediteranean Business Cooperation (Cooperative Management,, 2018)
This book brings together research on cooperative management from the agriculture and food sector. By examining issues from food-policy, trade and environmental perspectives and presenting both methodological and empirical work, it allows readers to develop a deeper understanding of collective management processes and cooperative initiatives, and provides a theoretical background for promoting research in the various sectors in which market communities operate. On a more global level the offers insights into how to building powerful tools for decision making, particularly at a time when agriculture and the economy alike are affected by a volatile political, social and economical environment and are forced to undergo major structural changes.